2002
DOI: 10.1046/j.1365-2842.2002.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentists' perceptions of dentine hypersensitivity and knowledge of its treatment

Abstract: The aim of the present investigation was to determine by questionnaire, UK dentists' perception of Dentine Hypersensitivity (DH) and knowledge of its treatment. A total of 403 questionnaires were sent to a selected group of UK dentists who had either inquired about further postgraduate education or had attended a course at the Eastman Dental Institute/Hospital. A total of 181 of 403 dentists (44.9%) (118M; 36F, 17 no response, mean age 38.2 years [s.d. 8.97]) returned the questionnaire. About 92.8% (n=168) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
54
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 10 publications
11
54
1
6
Order By: Relevance
“…Our study showed that the premolars were the most frequently affected teeth, followed by incisors and molars which is in agreement with many studies that showed the same results and it has been suggested that this distribution pattern of DH may be related to toothbrushing habits, while premolars and buccal surfaces are likely to receive more attention during brushing [16,43,44] .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed that the premolars were the most frequently affected teeth, followed by incisors and molars which is in agreement with many studies that showed the same results and it has been suggested that this distribution pattern of DH may be related to toothbrushing habits, while premolars and buccal surfaces are likely to receive more attention during brushing [16,43,44] .…”
supporting
confidence: 91%
“…The majority of practitioners participating in our survey described dentin hyperesthesia as a pulsatile pain, and 25,47% confirmed it its transitory character in agreement with many other studies [16,43,44] .…”
supporting
confidence: 89%
“…Overestimation might result from failure of the respondents to differentiate responses which followed true DH following erosive diet (either intrinsic or extrinsic) (16,17), with a much lower prevalence, from root sensitivity (RS), where it might be almost 100% (5,18). It could also be due to other underlying conditions for which sensitivity is a symptom such as cracked tooth syndrome, fractured restoration, marginal leakage and chipped teeth (16,19). Hence, the prevalence obtained might actually be overstating the prevalence of true DH.…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals are known to be more obsessive regarding toothbrushing habits, particularly those with dentin hypersensitivity, regularly brushing three or more times a day [82, 83] and for longer periods of time than the average population [84], again predisposing individuals to more likelihood of permanent trauma and recession. The gingival biotype is rarely mentioned in dentin hypersensitivity studies and reviews, yet places a major role in gingival surgery risk assessment of recession [85–87].…”
Section: Lesion Localisationmentioning
confidence: 99%